C2GAP2 is a common regulator of Ras signaling for chemotaxis, phagocytosis, and macropinocytosis - Xu, Xuehua; Pots, Henderikus; Gilsbach, Bernd K.; Parsons, Dustin; Veltman, Douwe M.; Ramachandra, Sharmila G.; Li, Haoran; Kortholt, Arjan; Jin, Tian (Frontiers in Immunology, 2022)
Phagocytosis, macropinocytosis, and G protein coupled receptor-mediated chemotaxis are Ras-regulated and actin-driven processes. The common regulator for Ras activity in these three processes remains unknown. Here, we show that C2GAP2, a Ras GTPase activating protein, highly expressed in the vegetative growth state in model organism Dictyostelium. C2GAP2 localizes at the leading edge of chemotaxing cells, phagosomes during phagocytosis, and macropinosomes during micropinocytosis. c2gapB− cells lacking C2GAP2 displayed increased Ras activation upon folic acid stimulation and subsequent impaired chemotaxis in the folic acid gradient. In addition, c2gaB- cells have elevated phagocytosis and macropinocytosis, which subsequently results in faster cell growth. C2GAP2 binds multiple phospholipids on the plasma membrane and the membrane recruitment of C2GAP2 requires calcium. Taken together, we show a shared negative regulator of Ras signaling that mediates Ras signaling for chemotaxis, phagocytosis, and macropinocytosis.